GEN Z’S PERSPECTIVE ON MICROMANAGING LEADERSHIP STYLE AND ITS IMPACT ON WORK PERFORMANCE - Nada Intan Salsabila; Anggara Wisesa; Irka Wijaya (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Currently, Generation Z in Indonesia has started to enter the workplace. This is an opportunity as well as a challenge for Indonesian society today and in the future. Therefore, it is necessary to prepare to welcome this new generation into the workforce, including considering what leadership styles can affect the business environment with this new generation. One of the leadership styles that may be adopted by leaders is micromanaging which is understood as a leadership style where the leader always wants to be involved in the work of subordinates; supervise subordinates carefully. Previous studies on the impact of micromanaging on Gen Z still show mixed results, therefore this study aims to understand Gen Z's perception of the micromanaging leadership style and its impact on their work performance. This study uses a qualitative phenomenological approach so that researchers can better understand Gen Z's perception of the micromanaging leadership style and its impact on their work performance based on their own experiences through in-depth interviews for data collection. From the perspective of Gen Z, micromanaging is perceived to have both positive and negative impacts on their work performance. Gen Z recognizes that micromanaging is necessary at this point in their careers with no work experience. Suggestions on how to manage micro Gen Z have been outlined and are part of this research.